Mentored conference experiences support students' career exploration and professional development - Elizabeth A. Flaherty; Casey C. Day; Rachael E. Urbanek; Darren M. Wood; Laura E. D'Acunto; Vanessa S. Quinn; Patrick A. Zollner (Wildlife Society Bulletin)
ABSTRACT Undergraduate students benefit when they gain awareness of the diversity of career opportunities within their field, explore their professional community, and develop professional social skills early. However, these opportunities are often limited to a few students who successfully compete for undergraduate research experiences (UREs), receive professional mentorship from graduate students, or participate in internships. National scientific conferences provide professional, academic, and social opportunities to a larger and more diverse population of undergraduate students than most UREs. However, unfamiliarity with the conference environment, including professional networking and socializing, may limit the overall proportion of undergraduate science students that attend and benefit from conference attendance. To address these concerns, we developed and assessed a formal undergraduate course that mentored students through their first professional scientific conference. Assessment results indicated that students made significant progress in their professional and social abilities, with many students expressing a new sense of belonging to their field. Based on these results, attending national scientific conferences provides undergraduate students with a supportive environment to explore their future career and develop professional social skills. An associated mentored course maximizes the potential for students to benefit from their conference experience. © 2019 The Wildlife Society.